Seleção de sistemas de tratamento de esgotos no âmbito de bacias hidrográficas a partir do emprego de modelagem de qualidade, otimização e da análise multiobjetivo - Bringer, Luiza Mayer (2017)
In Brazil, industrial and domestic wastewater disposal in watercourses constitutes one of the main factors responsible for water quality impacts in rivers. On the other hand, the individual or collective wastewater treatment before discharge into water courses represents the main strategy of pollution control. However, treatment efficiencies depend on receiving body's selfdepuration capacity, downstream water use characteristics and sewage characteristics and conditions. In order to determine required wastewater treatment plants efficiencies, water quality mathematical models and optimization techniques have been used in the sewage treatment systems process selection, usually aiming to achieve economic objectives. However, in water resources problem solving search involves multiple and conflicting objectives. This work used, for Pardo’s river basin (Espírito Santo, Brazil), water quality simulation model, optimization technique and multiobjective analysis for selecting sewage treatment systems. By reproducing QUAL-UFMG model mathematical formulations and conceptual and computational structures, the computational program developed in the MATLAB software, associated with the Genetic Algorithm, allowed the estimation of minimum organic matter removal efficiencies for the different points of effluent disposal in Pardo’s river basin, considering different disposal treated effluents scenarios. After a technical preselection stage, which considered three different possible wastewater treatment scenarios, a multiobjective analysis was applied by using theElectre III method, which selected sewage treatment systems for Ibatiba, Irupi, Iúna, Santíssima Trindade and Nossa Senhora das Graças urban areas, located in Pardo’s river basin. Treatment systems such as Rapid Infiltration, Submerged Aerated Biofilter (with Nitrification), Wetland, Facultative Ponds and UASB reactors (followed or not by post-treatment) were the most selected, considering the different drawn scenarios.